Application of edible topping as a salt reduction strategy in pizza pasta (Research, Society and Development, 2022)
Reducing salt has been strongly recommended by the World Health Organization (WHO), as the average daily intake of salt has been far above the level recommended by the WHO. The objective of this research was to reduce the sodium content in pizza dough, using a salty coating methodology that provided a non-homogeneous distribution of salt, so that the perception of salty taste was not altered, maintaining the sensory characteristics of the product. For this, 3 pizza dough formulations were elaborated and evaluated, being Formulation 1 (F1) the standard, Formulation 2 (F2) with a 30% reduction of salt in the whole dough, and, Formulation 3 (F3) without addition of salt in the dough, which was later added by means of salt topping. Physicochemical analyzes were performed regarding the salt intensity in the 3 pizza dough formulations. Sensory analysis was also performed using the 7cm unstructured scale, anchored at the extremes with terms of intensity, in order to evaluate and compare the salt intensity of the 3 pizza dough formulations. The salt content results showed significant differences between the samples. Regarding the sensory analysis, it was found that F1 and F3 did not show statistical differences in terms of sodium content, whereas F2 showed a difference between the others. With this, it was possible to conclude that the salt coating coating methodology can be an alternative for salt reduction without reducing the perception of salty taste.